2014
DOI: 10.3109/09637486.2014.917148
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selenium addition during germination ofBrassicaseeds on health-promoting potential of sprouts

Abstract: The correlation among selenium uptake, the content of bioactive compounds in sprouts, and biological activities triggered in cultured human cells by sprout extracts was investigated. Seeds of Brassica crops and rye were treated with SeO2 water solution. The selenium levels in sprouts increased from 1.0-4.1 to 53.3-382 μg/g dw with no influence on plant physiology according to the indices used. Neither the composition of glucosinolates (GL) in Brassica sprouts nor the myrosinase activity nor the composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 90 publications
2
36
0
Order By: Relevance
“…Sepúlveda et al (2013) reported that the myrosinase activity in mature broccoli is minimally affected by Se treatment. Piekarska et al (2014) also reported that the myrosinase activity in Brassica crops and rye decreases when treated with SeO 2 water solution (10 mg/L). This discrepancy can be attributed to different plant species, growth periods and Se concentrations.…”
Section: Effects Of Control Selenite and Selenate Treatments On Myromentioning
confidence: 93%
“…Sepúlveda et al (2013) reported that the myrosinase activity in mature broccoli is minimally affected by Se treatment. Piekarska et al (2014) also reported that the myrosinase activity in Brassica crops and rye decreases when treated with SeO 2 water solution (10 mg/L). This discrepancy can be attributed to different plant species, growth periods and Se concentrations.…”
Section: Effects Of Control Selenite and Selenate Treatments On Myromentioning
confidence: 93%
“…(2013) was adapted. An aliquot of vegetable sample (1 g consisting of 500 mg plant material and 500 mg of water) was weighted into a centrifugal tube, benzonitrile as internal standard (IST) was added, analytes were extracted with methylene chloride, and analyzed by GC-MS as described previously29 using a SGE BP5MS column 30 m × 0.25 mm × 0.25 μm (VWR International GmbH, Darmstadt, Germany). Analytes were identified by comparing mass spectra and retention times with those of authentic standards and with literature data30.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the contents of selenoglucosinolates exceeded those of their sulfur analogues in flower heads. In contrast to mature plants, no relationship between accumulation of Se and glucosinolates was A c c e p t e d M a n u s c r i p t 4 observed in selenized broccoli sprouts (Ávila et al, 2014;Carvacho et al, 2014;Piekarska et al, 2014). Dietary intake of Se-fertilized broccoli can increase serum Se concentration by 25%, but did not affect the concentrations of glucosinolate metabolites in plasma and urine compared to regular broccoli (Hauder et al 2011).…”
Section: Introductionmentioning
confidence: 93%